Phase Transformation and Enhancing Electron Field Emission Properties in Microcrystalline Diamond Films Induced by Cu Ion Implantation and Rapid Annealing - 申艳艳 张一新 祁婷 乔瑜 贾钰欣 黑鸿君 贺志勇 于盛旺 (Chinese physics letters, 2016)
Cu ion implantation and subsequent rapid annealing at 500℃ in N2 result in low surface resistivity of 1.611 ohm/sq with high mobility of 290 cm2 V-1S-1 for microcrystalline diamond （MCD） films. Its electrical field emission behavior can be turned on at Eo = 2.6 V/μm, attaining a current density of 19.5μA/cm2 at an applied field of 3.5 V/#m. Field emission scanning electron microscopy combined with Raman and x-ray photoelectron mi- croscopy reveal that the formation of Cu nanoparticles in MCD films can catalytically convert the less conducting disorder/a-C phases into graphitic phases and can provoke the formation of nanographite in the films, forming conduction channels for electron transportation.